Promoting Photovoice as a Tool and Guidance to Write - Sa’adah, Lailatus; Munir, Ahmad (ICONELT, 2023)
Writing a text is still regarded as one of the most difficult skills for students dealing with planning and organizing their ideas before beginning the actual writing process. However, a teacher should provide interesting activities to motivate students to solve those writing difficulties. As a critical pedagogy in education, because photovoice inspires students to express their perceptions, emotions, and learning experiences, it is possible to promote photovoice as a tool and writing guidance. It may help the students find an idea by using photographs, and following its guidance may lead the students to write.